2017
DOI: 10.4337/jhre.2017.02.03
|View full text |Cite
|
Sign up to set email alerts
|

The Declaration on Human Rights and Climate Change: a new legal tool for global policy change

Abstract: The Declaration on Human Rights and Climate Change responds to the profound crisis of human hierarchies now characterizing the climate crisis. The Declaration, initiated prior to the 2015 COP 21 meeting by scholars from the Global Network for the Study of Human Rights and the Environment (GNHRE), is one of a convergence of initiatives reflecting the need to understand human rights as intrinsically threatened by climate change. This article introduces the Declaration, the necessity for it, its philosophical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The transformative potential of rights-based approaches for climate decision-making remains far from realized, however. There are important gaps that need to be addressed to ensure that human rights are fully and effectively implemented in the processes and outcomes of climate governance at multiple levels [121,122]. In particular, there are several aspects of climate governance and issues of climate justice where the role and relevance of human rights require further clarification and innovation, including the recognition and protection of the rights of future generations [123], the human rights responsibilities of businesses in relation to climate change [124], and the contribution of human rights in efforts to enhance the climate resilience of populations [71,125,126].…”
Section: Discussionmentioning
confidence: 99%
“…The transformative potential of rights-based approaches for climate decision-making remains far from realized, however. There are important gaps that need to be addressed to ensure that human rights are fully and effectively implemented in the processes and outcomes of climate governance at multiple levels [121,122]. In particular, there are several aspects of climate governance and issues of climate justice where the role and relevance of human rights require further clarification and innovation, including the recognition and protection of the rights of future generations [123], the human rights responsibilities of businesses in relation to climate change [124], and the contribution of human rights in efforts to enhance the climate resilience of populations [71,125,126].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, he stated that SSI such as nuclear power plants, hydroelectric power plants, global warming, climate change, thermal power plants, and genetically modified organisms offer the necessary context for human rights education. On the other hand, attention was drawn to the relationship between human rights and numerous environmental aspects that were evaluated in the context of SSI in various studies (Akyuz, 2015a(Akyuz, , 2015bBenz, 2013;Clarke, 2010;Chang-Rundgren & Rundgren, 2010;Colakoglu, 2010;Davies et al, 2017;Demirdelen & Odman, 2017;Dolan et al, 2009;Evren-Yapicioglu, 2018;Kadioglu, 2008;Moro, 2002;Ziya, 2012;Rademacher, 2010;Yardimoglu, et al, 2014) in the related literature. This supports the claim advocated in this study that SSI can be an effective context for human rights education as part of environmental education courses.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Academics have suggested that States should ensure "effective remedies in administrative or judicial proceedings for climate harm or the threat or risk of such harm, including modes of compensation, monetary or otherwise [68]". Indeed, States are obliged to ensure access to effective remedies for violations of the right to health, including those occurring in connection with climate change [33,[51][52][53]69].…”
Section: United Nations Human Rights Forums For Seeking Redress For I...mentioning
confidence: 99%